Pengaruh Metode Pembelajaran Mimicry Memorization Terhadap Motivasi dan Hasil Belajar Bahasa Arab - Uswatun Khasanah; Silviana Faizah (Islamic Elementary School Teacher Education Study Program, Faculty of Education and Teacher Training, K.H. Abdurrahman Wahid Pekalongan State Islamic University, Indonesia, 2024)
The research aims to investigate the impact of the Mimicry Memorization (MIM-MEM) method on learning motivation and Arabic study results. The study employed an experimental design with a single-group pretest and posttest, supported by test questions, questionnaires, motivation learning assessments, and documentation as instruments. Data analysis utilized descriptive statistical techniques, including scoring, mean, and N-Gain. Subsequently, statistical tests, such as the normality test and paired sample t-test, were conducted to test the hypotheses. The findings reveal a significant influence of the Mimicry Memorization (MIM-MEM) method on student learning motivation. This is evident in the observed increase in student learning motivation (37.17) and N-Gain (0.42), both falling within the medium category. The paired sample t-test yielded a significance value of 0.000. Moreover, the research demonstrates a notable impact of the Mimicry Memorization (MIM-MEM) method on student learning outcomes. The data indicates an increase in student learning motivation (40.67) and N-Gain (0.43), both categorized as medium. The paired sample t-test yielded a significance value of 0.000. In conclusion, the Mimicry Memorization (MIM-MEM) method proves to be an effective alternative for learning Arabic, enhancing both learning motivation and student outcomes.